Microscopic shape from focus using white light interferometric fringes (2018)
In this work we study the use of a focus measure to improve the 3D reconstruction of low reflectivity microscopic samples using white light interference microscopy. Simulation and experimental results show the improved reconstruction. © 2018 The Author(s).